The Lower Limit of Reference of Urinary Albumin/Creatinine Ratio and the Risk of Chronic Kidney Disease Progression in Patients With Type 2 Diabetes Mellitus - Tang, Wei-Hua; Hung, Wei-Chin; Wang, Chao-Ping; Wu, Cheng-Ching; Hsuan, Chin-Feng; Yu, Teng-Hung; Hsu, Chia-Chang; Cheng, Ya-Ai; Chung, Fu-Mei; Lee, Yau-Jiunn; Lu, Yung-Chuan (Frontiers in Endocrinology, 2022)
A urine albumin/creatinine ratio (UACR) <30 mg/g is considered to be normal, while increased risk of incident hypertension and cardiovascular disease mortality in subjects with high normal UACR level had been observed. However, a mild elevated but normal UACR level was associated with the risk of initiating chronic kidney disease (CKD) is uncertain. We investigated whether higher normal UACR is associated with the risk of developing CKD. A total of 4821 subjects with type 2 diabetes mellitus (T2DM), an estimated glomerular filtration rate >60 ml/min/1.73 m2 and UACR <30 mg/g enrolled in a diabetes disease management program between 2006 and 2020 were studied. The optimal cutoff point for baseline UACR as a predictor for progression to CKD according to the 2012 KDIGO definition was calculated using receiving operating characteristic curve analysis. After a mean of 4.9 years follow-up, the CKD risk progression increased in parallel with the quartiles of baseline UACR <30 mg/g (p for trend <0.0001). UACR cutoff points of 8.44 mg/g overall, 10.59 mg/g in males and 8.15 mg/g in females were associated with the risk of CKD progression. In multivariate Cox regression analysis, the hazard ratios for the association between UACR (>8.44 mg/g, >10.9 mg/g, >8.15 mg/g in overall, male, and female patients, respectively) and the risk of CKD progression were significant. This study demonstrated that a cutoff UACR value of >10 mg/g could significantly predict the cumulative incidence and progression of CKD in patients with T2DM.